La necesaria imbricación entre aprendizaje y formación. El simulador situativo como tecnología adecuada para la formación de formadores. - García Fraile, Juan Antonio; Domínguez Fernández, Guillermo; Biencinto López, Chantal (Revista Complutense de Educación, 2006)
The way to focus the learning has undergone important modifications throughout the history of the education. If in the traditional model protagonism were represented by the content to transmit and the person in charge to do it now (teacher) it will fall to which learn (student) and to the method. The change with respect to the traditional model piloted by the New School was in lending priority to the methods or forms to make on the contents or forms to know. From then will be more important the knowledge to make that the knowledge in himself. For that reason the activities will have like purpose of learning methods. Of this form, the education will have to be based on the respect to the interests and necessities of the people who learn, using active methods, developing the autonomy, the critical spirit and the cooperation of these.